Estimating of Pore Pressure Gradient in Lower Fars Formation - F. Hussain, Neaam; H. M. Al Mahdawi, Faleh (Iraqi Journal of Chemical and Petroleum Engineering, 2018)
In petroleum industry, the early knowledge of “pore pressure gradient” is the basis in well design and the extraction of these information is more direct when the pore pressure gradient is equal to normal gradient; however, this matter will be more complex if it deviate from that limit which is called “abnormal pore pressure”, if this variable does not put in consideration, then many drilling problems will occur might lead to entire hole loss. To estimate the pore pressure gradient there are several methods, in this study; Eaton method’s is selected to extract the underground pressure program using drilling data (normalized rate of penetration) and logs data (sonic and density log). The results shows that an abnormal high pressure is observed in Lower Fars formation started from Mb5 member as a transition zone and increase gradually until reach the Mb4 member and continuous to Mb3 and Mb2 then begin to decrease from Mb1 which is consider a transition zone between high pore pressure zone and sub-pressure zone represented by Jeribe-Euphrate and Upper Kirkuk formations and back to normal pore pressure at Middle-Lower Kirkuk formation. The dc-exponent method has been selected in estimating pore pressure gradient and considers the best one compared with logs data methods.